Unleashing the potentials of desktop virtual reality as an educational tool : A look into the design and development process of ViSTREET - Chuah, Kee Man; Chen, Chwen Jen (2008)
The advancement in personal desktop computers and the advent of broadband Internet have prompted many researchers and educators to explore various learning opportunities through virtual reality particularly via desktop-based virtual environments. To fully uncover the potentials of virtual reality, one fundamental issue that needs further investigation and is addressed in this paper is to identify the appropriate instructional design models to guide its design and development. In this work, an instructional design and development framework is chosen to guide the design of an on-going project known as ViSTREET (Virtual Simulated Traffic for Road Safety Education), which aims to solve a learning problem related to children pedestrian safety skills through virtual learning environments. The paper provides an elaboration of how various components of the learning environments are designed in line with the prescribed framework. This study has managed to highlight the advantages of using the chosen framework to guide the design and development of virtual learning environments particularly its incorporation of constructivist principles and problem-based learning that can help to enhance learner’s learning experience. In addition, the outcomes of this work also provide further confirmation on the vast potentials of virtual reality technology for educational purposes.